Hydroxymethylation of unsaturated hydrocarbons with CO2: An overview. Issue 50 (August 2021) - Wang, Xiang; Ping, Wei; Ebadi, Abdol Ghaffar; Majedi, Soma; Hossaini, Zinatossadat; Toughani, Mohsen
Highlights: Advances and developments of the direct hydroxymethylation of unsaturated hydrocarbons using CO2 as the carbonylation source. New catalytic systems and reducing agents for one-pot hydroxymethylation of unsaturated CC bonds with CO2 . The issues of the synthesis of hydroxymethyl-alcohols. Insightful mechanistic discussions. Abstract: The objective of this review is to summarize recent progress and advances in the synthesis of hydroxymethyl-alcohols through the direct hydroxymethylation of unsaturated hydrocarbons using CO2 as the carbonyl source with insightful mechanistic discussions. Depending on the unsaturated substrates employed the paper is divided into three sections. The first section focuses exclusively on hydroxymethylation of alkenes. The second covers hydroxymethylation of allenes. The third section gives a brief overview of the hydroxymethylation of alkynes.